Rising cost of antidotes in the U.S.: cost comparison from 2010 to 2015. (28th May 2017) - Heindel, Gregory A.; Trella, Jeanette D.; Osterhoudt, Kevin C.
Abstract: Context: Our poison control center observed a large increase in the cost of many antidotes over the past several years. The high cost of antidotes has previously been cited as a factor leading to inadequate antidote supply at some hospitals. Continued increases in the cost of antidotes may lead to further reductions in antidote supply and represent serious concerns. This research aims to quantify recent trends in the costs of antidotes in the U.S. Methods: Antidotes and minimum stocking recommendations were retrieved from published guidelines. RED BOOK Online ® was used to identify the U.S. average wholesale price (AWP) of each antidote in 2010 and 2015. The AWP in 2010 was adjusted using the U.S. Consumer Price Index to adjust for inflation. The cost of minimum stocking levels for each antidote was calculated and compared between the year 2010 and 2015. Results: The cost of stocking many antidotes demonstrated a large increase in AWP from 2010 to 2015. Of the antidotes evaluated, 15 out of 33 had greater than 50% increase in AWP and 8 out of 33 had greater than 1000 increase in AWP. Only four antidotes demonstrated decreases in AWP greater than 10% and only one antidote had its cost of stocking decrease in AWP by more than 1000. Discussion: The price increase over the last 5 years may further hinder the willingness of hospitals to stock recommended antidotes at adequate quantities. This may impede timely treatment of patients, and negatively impact poisoning outcomes. Conclusions: The price of many antidotes substantially increased in the United States from 2010 to 2015. Strategies should be investigated to help decrease the cost associated with stocking and use of antidotes, including dose rounding, consignment, and regional sharing.